Wind farm array cable layout optimisation for complex offshore sites—A decomposition based heuristic approach - Peter Taylor; Hong Yue; David Campos‐Gaona; Olimpo Anaya‐Lara; Chunjiang Jia (IET Renewable Power Generation, 2023)
Abstract As the number of turbines in offshore wind farms increases, so does the complexity of cable routing optimisation problems. Optimising the collector network is a crucial task for developers contributing between 15% and 30% of initial investment costs. For some algorithms, increasing the number of turbines leads to unfavourable scaling of the computational time and memory required to reach optimal solutions. Heuristics offer an alternative but are likely to incur increases in total costs relative to the optimal solution since heuristic searching cannot guarantee optimality. This study proposes a novel optimisation algorithm based on the ant‐colony heuristic by introducing decomposition techniques informed by the problem formulation to improve the computational performance. The new algorithm can reach near‐optimal solutions and requires little computational resource. Three algorithms are compared on a set of six case studies, including mixed‐integer linear programming (MILP), classical ant‐colony optimisation (ACO) algorithm, and the proposed ACO with decomposition, ACOsp. Optimal solutions were found using the MILP algorithm. ACO algorithm solutions cost 0.4–7.6% more than optimal solutions, whereas ACOsp solutions cost only 0.0–1.4% more than optimal solutions. The proposed ACOsp algorithm has shown to be a robust approach for large‐scale cable layout optimisation problems (>100 turbines) without requiring high‐performance computing facilities.